Price of duty - Strasser, Todd (Simon & Shuster Books for Young Readers, 2018)
War hero Jake Liddell is being considered for the award of the Silver Star, a huge accomplishment and honor for any member of the military, but especially as he is the son of a military family. However, Jake, haunted from his experiences from "over there," is questioning everything he believes as contradictions come from all sides of his life--his friends want him to speak against the military, but his war-hero grandfather wants him to go back and serve again. Jake wants to believe his country is morally in the right, but he can't help but question it now he knows what fighting for it is like firsthand.